176 Are Ovarian Reserve Parameters Related to Reproductive Tract Development and Fertility in Ewes?. (12th April 2022) - Cushman, Robert; Yake, Hannah K; Snider, Alexandria P; Murphy, Thomas; Freking, Bradley
Abstract: There are differences between cows and ewes in ovarian reserve parameters. No major genes influencing follicle numbers have been identified in cows, whereas several genes have variants reported to influence follicle numbers in ewes. In contrast, antral follicle count is associated with fertility in cows, and we reported that beef cows that failed to conceive in 2 consecutive years had fewer antral follicles and smaller reproductive tracts than cows that had never failed to conceive. In the current study, we tested the hypothesis that ewes that had failed to lamb (BARREN) in 4 consecutive annual breeding seasons of 21– 35 d with rams that had passed a breeding soundness exam have fewer follicles and smaller reproductive tracts than ewes that consistently produced lambs (FERTILE) under the same breeding protocols. BARREN ewes (n = 19) were paired by breed, age, and sire to a FERTILE control ewe (n = 19) and reproductive tracts were recovered at necropsy. All visible antral follicles in both ovaries were counted and a representative cross section of one ovary was embedded for histological evaluation of primordial follicle numbers. The reproductive tract was weighed, and ovulatory status was evaluated. Paired t-tests indicated that BARREN ewes had 25.6 ± 5.0 fewer antral follicles per pair of ovaries, 17.3 ± 4.4 fewer primordial follicles per histological section, and 54.5 ± 18.7 g lighter reproductive tracts than FERTILE ewes ( P ≤ 0.01). The odds of FERTILE ewes being ovulatory at necropsy were 2.25 that of BARREN ewes, but this did not differ from expectation by McNemar's test ( P = 0.13). The results indicate that size of the ovarian reserve influences fertility in ewes as it does in cows. USDA is an equal opportunity provider and employer.